Clinical Findings Associated with a De Novo Partial Trisomy 10p11.22p15.3 and Monosomy 7p22.3 Detected by Chromosomal Microarray Analysis - Kohannim, Omid; Peredo, Jane; Dipple, Katrina M.; Quintero-Rivera, Fabiola (Case Reports in Genetics, 2011)
We present the case of an 18-month-old boy with dysmorphic facial features, developmental delay, growth retardation, bilateral clubfeet, thrombocytopenia, and strabismus, whose array CGH analysis revealed concurrent de novo trisomy 10p11.22p15.3 and monosomy 7p22.3. We describe the patient's clinical presentation, along with his cytogenetic analysis, and we compare the findings to those of similar case reports in the literature. We also perform a bioinformatic analysis in the chromosomal regions of segmental aneuploidy to find genes that could potentially explain the patient's phenotype.